FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA AKUNTANSI DALAM PENGAMBILAN CERTIFIED PUBLIC ACCOUNTANT - Wennita, Wennita; Wangdra, Ronald (LPPM Universitas Putera Batam, 2025)
The Certified Public Accountant (CPA) certification is a crucial step for accounting students to enhance their credibility and career prospects in the accounting field. However, the low interest of students in taking the CPA exam remains a challenge. This study aims to analyze the influence of career motivation, financial rewards, and labor market considerations on the interest of accounting students in pursuing CPA certification. The research adopts a quantitative approach using a survey design targeting accounting students from various universities in Batam City. The results indicate that all three independent variables significantly influence student interest, both partially and simultaneously. These findings have implications for universities and stakeholders to raise awareness and motivate students to pursue CPA certification. Keywords: Career Motivation, Financial Rewards, Labor Market Considerations, Certified Public Accountant, Student Interest.